Factors affecting the communicative interaction among students of the Foreing Language Departament out of classrooms - Pérez Arana, Lorena Beatríz (Universidad de El Salvador, 2004)
Practice is a critical aspect in successful learning, especially when referring to language learning. The present essay is an analysis of the factors that affect the communicative interaction in the English language among students of the B.A. in English out of classrooms. In order to have a better analysis, these factors have been classified in three categories: Personality factors, Social factors and Cultural factors. Next, based on the bibliographical research and in the investigation made in the last months it is presented a general description of the main aspects implicit in each category that are affecting in this matter. The lack of practice of English language among students of the Foreign Language Department out of classrooms is a problem caused by: Personality, Social and Cultural factors